ANALISIS KESETARAAN GENDER PADA ANAK USIA DINI DI PAUD ISLAM AL-AZZAM BABAT SUPAT TAHUN AJARAN 2024/2025 - Santa Idayana Sinaga; Lailatul Hasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation and perceptions of educators regarding gender equality in the learning process at Al-Azzam Islamic Early Childhood Education Center, Babat Supat Subdistrict, Musi Banyuasin Regency. Using a qualitative approach with a case study method, data was collected through interviews, observations, and documentation of teachers and 4-year-old students. The results of the study indicate that educators have applied the principle of gender equality in learning, such as providing equal opportunities for boys and girls to participate in various activities and class roles. However, it was found that children's preferences in play are still influenced by gender stereotypes originating from the social environment. In addition, learning media show progress in gender role representation, although it is not yet fully consistent. Teachers' perceptions of gender equality are generally positive, but they still face cultural challenges and limitations in parental participation. This study concludes that Al-Azzam Islamic PAUD is in a transitional stage toward becoming a gender-responsive educational institution. The implications of this study emphasize the importance of teacher training, the development of inclusive learning media, and collaboration with parents and the community in shaping awareness of gender equality from an early age.